Anda di halaman 1dari 1

𝟒𝒙+𝟓

Dada la función 𝑭(𝒙) =


𝟑𝒙𝟐 +𝟐
𝑭(𝒙+𝒉)−𝑭(𝒙)
Hallar su derivada aplicando la definición 𝑳𝒊𝒎
𝒉→𝟎 𝒉
Solución:
𝑭(𝒙+𝒉)−𝑭(𝒙)
𝑭′ (𝒙) = 𝑳𝒊𝒎
𝒉→𝟎 𝒉
𝟒(𝒙+𝒉)+𝟓
𝟐
− 𝟒𝒙+𝟓
𝟐
𝟒𝒙+𝟒𝒉+𝟓
− 𝟒𝒙+𝟓
𝟑(𝒙+𝒉) +𝟐 𝟑𝒙 +𝟐 𝟐 𝟐
′ (𝒙) 𝟑𝒙𝟐+𝟔𝒙𝒉+𝟑𝒉 +𝟐 𝟑𝒙 +𝟐
𝑭 = 𝐋𝐢𝐦 ( ) = 𝐋𝐢𝐦 ( )
𝒉→𝟎 𝒉 𝒉→𝟎 𝒉

𝟐 𝟐
𝟏𝟐𝒙𝟑 +𝟖𝒙+𝟏𝟐𝒙𝟐𝒉+𝟖𝒉+𝟏𝟓𝒙𝟐 +𝟏𝟎−(𝟏𝟐𝒙𝟑+𝟏𝟓𝒙𝟐 +𝟐𝟒𝒙𝟐𝒉+𝟑𝟎𝒙𝒉+𝟏𝟐𝒙𝒉 +𝟏𝟓𝒉 +𝟖𝒙+𝟏𝟎)
𝟐 𝟐
𝟗𝒙𝟒 +𝟔𝒙𝟐+𝟏𝟖𝒙𝟑 𝒉+𝟏𝟐𝒙𝒉+𝟗𝒙𝟐𝒉 +𝟔𝒉 +𝟔𝒙𝟐+𝟒
𝐋𝐢𝐦
𝒉→𝟎 𝒉

( )
𝟐 𝟐
𝟏𝟐𝒙𝟑+𝟖𝒙+𝟏𝟐𝒙𝟐 𝒉+𝟖𝒉+𝟏𝟓𝒙𝟐+𝟏𝟎−𝟏𝟐𝒙𝟑−𝟏𝟓𝒙𝟐 −𝟐𝟒𝒙𝟐𝒉−𝟑𝟎𝒙𝒉−𝟏𝟐𝒙𝒉 −𝟏𝟓𝒉 −𝟖𝒙−𝟏𝟎
𝟐 𝟐
𝟗𝒙𝟒 +𝟔𝒙𝟐+𝟏𝟖𝒙𝟑 𝒉+𝟏𝟐𝒙𝒉+𝟗𝒙𝟐𝒉 +𝟔𝒉 +𝟔𝒙𝟐+𝟒
𝐋𝐢𝐦 ( )
𝒉→𝟎 𝒉

𝟐 𝟐
−𝟏𝟐𝒙𝟐𝒉+𝟖𝒉−𝟑𝟎𝒙𝒉−𝟏𝟐𝒙𝒉 −𝟏𝟓𝒉
𝟐 𝟐
𝟗𝒙𝟒 +𝟔𝒙𝟐 +𝟏𝟖𝒙𝟑𝒉+𝟏𝟐𝒙𝒉+𝟗𝒙𝟐𝒉 +𝟔𝒉 +𝟔𝒙𝟐+𝟒
𝐋𝐢𝐦 ( )
𝒉→𝟎 𝒉

−𝟏𝟐𝒙𝟐 𝒉+𝟖𝒉−𝟑𝟎𝒙𝒉−𝟏𝟐𝒙𝒉𝟐 −𝟏𝟓𝒉𝟐 𝒉


𝐋𝐢𝐦 ( 𝟒 𝟐 ÷ )
𝒉→𝟎 𝟗𝒙 +𝟔𝒙 +𝟏𝟖𝒙𝟑 𝒉+𝟏𝟐𝒙𝒉+𝟗𝒙𝟐 𝒉𝟐 +𝟔𝒉𝟐 +𝟔𝒙𝟐 +𝟒 𝟏

𝒉 (−𝟏𝟐𝒙𝟐 +𝟖−𝟑𝟎𝒙−𝟏𝟐𝒙𝒉−𝟏𝟓𝒉)
𝐋𝐢𝐦 ( (𝟗𝒙𝟒 𝟐 )
𝒉→𝟎 𝒉 +𝟔𝒙 +𝟏𝟖𝒙𝟑 𝒉+𝟏𝟐𝒙𝒉+𝟗𝒙𝟐 𝒉𝟐 +𝟔𝒉𝟐 +𝟔𝒙𝟐 +𝟒)

−𝟏𝟐𝒙𝟐 +𝟖−𝟑𝟎𝒙−𝟏𝟐𝒙𝒉−𝟏𝟓𝒉
𝐋𝐢𝐦 ( 𝟒 𝟐 )
𝒉→𝟎 𝟗𝒙 +𝟔𝒙 +𝟏𝟖𝒙𝟑 𝒉+𝟏𝟐𝒙𝒉+𝟗𝒙𝟐 𝒉𝟐 +𝟔𝒉𝟐 +𝟔𝒙𝟐 +𝟒

–𝟏𝟐𝒙𝟐 +𝟖−𝟑𝟎𝒙−𝟏𝟐𝒙𝒉−𝟏𝟓𝒉
𝐋𝐢𝐦
𝒉→𝟎 𝟗𝒙𝟒 +𝟔𝒙𝟐 +𝟏𝟖𝒙𝟑 𝒉+𝟏𝟐𝒙𝒉+𝟗𝒙𝟐 𝒉𝟐 +𝟔𝒉𝟐 +𝟔𝒙𝟐 +𝟒

−𝟏𝟐𝒙𝟐 +𝟖−𝟑𝟎𝒙−𝟏𝟐𝒙(𝟎)−𝟏𝟓(𝟎) −𝟏𝟐𝒙𝟐 −𝟑𝟎𝒙+𝟖


= =
𝟗𝒙𝟒 +𝟔𝒙𝟐 +𝟏𝟖𝒙𝟑 (𝟎)+𝟏𝟐𝒙(𝟎)+𝟗𝒙𝟐 (𝟎)𝟐 +𝟔(𝟎)𝟐 +𝟔𝒙𝟐 +𝟒 𝟗𝒙𝟒 +𝟏𝟐𝒙𝟐 +𝟒

−𝟏𝟐𝒙𝟐 −𝟑𝟎𝒙+𝟖
= (𝟑𝒙𝟐 +𝟐)𝟐

Comprobación
(𝟑𝒙𝟐 +𝟐)(𝟒)−(𝟒𝒙+𝟓)(𝟔𝒙) 𝟏𝟐𝒙𝟐 +𝟖−𝟐𝟒𝒙𝟐 −𝟑𝟎𝒙
𝑭′ (𝒙) = =
(𝟑𝒙𝟐 +𝟐)𝟐 (𝟑𝒙𝟐 +𝟐)𝟐

−𝟏𝟐𝒙𝟐 −𝟑𝟎𝒙+𝟖
𝑭′ (𝒙) = L.Q.A.G.Q.D
(𝟑𝒙𝟐 +𝟐)𝟐